KEKERASAN DALAM RUMAH TANGGA (KDRT) DALAM NOVEL PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH EL KHALIEQY - Winda Fitrah Khalbina; Novia Juita; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purpose of this study is to describe the violence in character of the novel Perempuan Berkalung Sorban by Abidah El Khalieqy. This data is a quote that contain of violence on figures in this novelPerempuan Berkalung Sorban by Abidah El Khalieqy . The method is used to collect the data is read and written. The data is collected with the following steps: (1) read the novel Perempuan Berkalung Sorban by Abidah El Khalieqy, (2) analyzing the violence contained in the novel Perempuan Berkalung Sorbanby Abidah El Khalieqy, (3) especially to study literature references related to the research problem, (4) writing related data of the violence, (5) make the conclusion. Based on the research findings and discussion it can be concluded that a character in the novel Perempuan Berkalung Sorbanby Abidah El Khalieqy, is classified on the main character and additional character. The main character in thisnovel Perempuan Berkalung Sorban by Abidah El Khalieqy is Annisa. The additional character are Samsudin, Kalsum, Khudhori, Kiai Hanan Abdul Malik, Hajjah Mutmainah, Rizal, Wildan, Nina, Maryam, and Fauziah.